Enigmas of sacrifice: a critique of Joseph M. Plunkett and the Dublin Insurrection of 1916 - McCormack, William J. (Studies in Violence, Mimesis, & Culture, 2016)
Enigmas of Sacrifice: A Critique of Joseph M. Plunkett and the Dublin Insurrection of 1916 is the first critical study of the religious poet and militarist Joseph M. Plunkett, who was executed with the other leaders of the Dublin insurrection of 1916. Through Plunkett the author gains access to areas of nationalist thought that were more often assumed or repressed than publicly formulated. In this eye-opening book, W.J. Mc Cormack explores and analyzes Plunkett's brief life, work, and influence, beginning with his wealthy but dysfunctional family, irregular Jesuit education, and self-canceling sexuality. Mc Cormack continues through Plunkett's active phase when amateur theatricals and a magazine editorship brought him into the emergent neonationalist discourse of early twentieth-century Ireland. Finally, the author arrives at Holy Week 1916, when Plunkett masterminded the forgery of official documentation in order to provoke and justify the insurrection he planned. Mc Cormack analyzes Plunkett's significant texts and provides context through critical perspectives on his milieu. Enigmas of Sacrifice is unique in its effort to understand a major figure of Irish nationalism in terms that reach beyond political identity